The Correlation Between Exposure to Cigarette Smoke and The Incidence of Anemia during Pregnancy - Martini, Diah Eko; Rini, Evi Jihan Sulistyo; Kusbiantoro, Dadang; susanti, Inta (Universitas Muhammadiyah Lamongan, 2023)
Introduction: Anemia is a common hematological disorder in pregnancy which causes a decrease in hemoglobin levels, this has the risk of increasing morbidity and mortality. Exposure to cigarette smoke may be one of the factors that contributes to a decrease in hemoglobin levels in pregnant women. This study aims to determine the correlation between exposure to cigarette smoke and the incidence of pregnancy anemiaMethod: This research uses correlational analytics with a cross sectional approach. The population was all pregnant women in the third trimester who were exposed to cigarette acid in their homes with a total sample of 35 people taken using purposive sampling. Data was collected through interviews regarding the frequency of exposure, then peripheral hemoglobin levels were measured and then tested using Spearman Rho analysis.Results: The results showed that pregnant women who had light exposure to cigarette smoke tended to have no anemia (87.5%), while the majority of pregnant women who had moderate exposure to cigarette smoke had mild anemia (60%), and mothers who had moderate exposure to cigarette smoke had mild anemia (60%). The majority of heavy smokers have moderate anemia (55.6%). The average hemoglobin level in light exposure to cigarette smoke tends to be higher than the hemoglobin level in moderate and heavy exposure with a risk factor probability of 19,5. These results are strengthened by the Spearman rho test with a value of p = 0.000 (P<0.05), r = 0.777, this finding proves that exposure to cigarette smoke has a strong correlation with the incidence of pregnancy.Conclusion: Exposure to cigarette smoke has been proven to be a risk factor for decreasing hemoglobin levels and causing anemia in pregnancy.Keywords: exposure to cigarette smoke; pregnancy anemia; Hemoglobin levels